STRAIN-RATE EFFECT ON THE STRESS CONCENTRATION IN A 45 STEEL PLATE WITH AN ELLIPTIC HOLE - ZHANG Jin; WU Jian; WANG WeiBo; YU PeiShi; ZHAO JunHua (Jixie qiangdu)
Stress concentration caused by holes in a component is always an important research topic in structural safety assessment. Many studies have been carried out on linear elastic materials under static loading,including the effects of hole shape,material anisotropy and loading direction on stress concentration. However,the coupling effect of the nonlinear stressstrain relationship and the strain-rate effect will lead to a great difference between the stress concentration for the plastic material and the existing linear elastic results when the material is under dynamic loading,especially for many kinds of metal materials with plastic deformation. Therefore,based on the Johnson-Cook model,the stress concentration at the hole root of a typical 45 steel plate under dynamic loading is systematically analyzed using finite element method. The results show that the plastic stress concentration factor depends not only on the loading magnitude（ strain） but also on the loading speed（ strain rate）. For the plate at plane stress state under the remote strain of 1%,the stress concentration factor at the circle hole for ε∞= 20/s is around 10%higher than that for ε∞= 0. 1/s,while the stress concentration factor at the elliptic hole with the shape factor（ minor axis/major axis） of 0. 5 for ε∞= 20/s is around 11% higher than that for ε∞= 0. 1/s.